Convergent vegetation fog and dew water use in the Namib Desert. Issue 7 (15th July 2019) - Wang, Lixin; Kaseke, Kudzai Farai; Ravi, Sujith; Jiao, Wenzhe; Mushi, Roland; Shuuya, Titus; Maggs‐Kölling, Gillian
Abstract: Nonrainfall water inputs (e.g., fog and dew) are the least studied hydrological components in ecohydrology. The importance of nonrainfall waters on vegetation water status in arid ecosystems is receiving increasing attention. However, a clear understanding on how common plant water status benefits from nonrainfall waters, the impacts of different types of fog and dew events on vegetation water status, and the vegetation uptake mechanisms of nonrainfall waters is still lacking. In this study, we used concurrent leaf and soil water potential measurements from 3 years to investigate the species‐specific capacity to utilize moisture from fog and dew within the Namib Desert. Eight common plant species in the Namib Desert were selected. Our results showed that both fog and dew significantly increased soil water potential. Seven of the eight plant species studied responded to fog and dew events, although the magnitude of the response differed. Plants generally showed stronger responses to fog than to dew. Fog timing seemed to be an important factor determining vegetation response; for example, night fog did not affect plant water potential. We also found that Euclea pseudebenus and Faidherbia albida likely exploit fog moisture through foliar uptake. This study provides a first comprehensive assessment of the effects of nonrainfall waters on plant water status within the Namib Desert. Furthermore, this study highlights the importance of concurrent leaf and soil water potential measurements to identify the pathways of nonrainfall water use by desert vegetation. Our results fill a knowledge gap in dryland ecohydrology and have important implications for other drylands.